ETHICAL DIMENSIONS OF PARTICIPANT SELECTION IN SENSITIVE SOCIAL RESEARCH - Onawo, Hussaini Yusuf (African Journal of Social and Behavioural Sciences, 2025)
This conceptual review examines the ethical frameworks and principles that guide participant selection in sensitive social research contexts. Through a critical review of existing literature on research ethics, sampling methodologies, and the protection of vulnerable groups, it identifies key ethical tensions in sample selection and proposes a framework for ethically responsible participant recruitment. Sensitive research, characterised by studies involving vulnerable populations, stigmatised behaviours, or emotionally charged topics, presents unique ethical challenges in determining participant eligibility and recruitment methods. This paper synthesizes ethical principles from the Belmont Report, institutional review board guidelines, and current scholarship to demonstrate how informed consent, beneficence, justice, and cultural sensitivity influence sampling decisions. The analysis reveals that ethical sample selection necessitates balancing scientific rigor with participant protection, ensuring inclusivity without exploitation, and maintaining confidentiality while achieving representative samples. This study contributes to the discourse on research ethics by offering a comprehensive ethical framework focused on the often-overlooked issue of participant selection in sensitive research, along with practical guidance for researchers, ethics committees, and institutional review boards.